Implementasi Kebijakan Transaksi Non Tunai Pemerintah Daerah di Indonesia - Astri Tania Herlen; Vima Tista Putriana; Denny Yohana (Universitas Batanghari Jambi, 2021)
Non cash transactions are a new paradigm in the management of government finance. Non cash transactions are implemented in line with the issuance of the Minister of Home Affairs circular No. 910/1866 in 2017 concerning the implementation of non cash transactions in local governments. This is in accordance with the provisions of Presidential Instruction No. 10 in 2016. The purpose of this study is to investigate the application of non cash transactions by local governments in Indonesia. The results showed that the implementation varies across local governments in Indonesia in terms of when local governments under studied began to implement the system, minimum amount or threshold for the cash transactions allowed by the local governments under studied and types of transactions that have been done under non-cash transactions. The implementation of the non cash system is carried out in accordance with the principles of good governance. This non cash transaction system provides several benefits and constraints in implementing it in local governments